QUANTITATIVE EBIC INVESTIGATIONS OF DEFORMATION-INDUCED AND COPPER DECORATED DISLOCATIONS IN SILICON - Fell, T; Wilshaw, P (Publ by Inst of Physics Publ Ltd, 1991)
Deformation induced dislocations in silicon have been found to exhibit different degrees of electrical activity dependent upon whether they were deformed at 420°C or 650°C. Furthermore the effects of copper decoration are also found to vary between dislocations produced at these temperatures. Quantitative analysis of EBIC measurements in terms of the charge at dislocations reveals this behaviour to be due to different defect states.